2022
DOI: 10.1093/jac/dkac401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the acute phase of infection on absorption of and exposure to orally administered antibiotics in non-critically ill, hospitalized patients

Abstract: Objectives During the acute phase of infection, IV antibiotics are preferred to ensure adequate systemic exposure. To assess whether adequate exposure may also be achieved with oral antibiotics, we investigated exposure to oral antibiotics and PTA during the acute phase of infection and after defervescence. Methods We enrolled hospitalized, non-critically ill febrile patients treated with IV antibiotics other than amoxicillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Oral treatment of CAP has already been widely evaluated and implemented for the treatment of mild-to-moderate cases 6 – 10 , 13 . However, the role of oral antibiotics in the upfront treatment of more severe cases has not been sufficiently assessed despite the high bioavailability of oral antibiotics like amoxicillin, doxycycline and moxifloxacin 17 19 , 35 . Only two studies with a large majority of moderate-to-severe CAP patients showed similar or even better outcomes for oral treatment compared to intravenous treatment, but did not specify the disease severity for patients with treatment failure 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Oral treatment of CAP has already been widely evaluated and implemented for the treatment of mild-to-moderate cases 6 – 10 , 13 . However, the role of oral antibiotics in the upfront treatment of more severe cases has not been sufficiently assessed despite the high bioavailability of oral antibiotics like amoxicillin, doxycycline and moxifloxacin 17 19 , 35 . Only two studies with a large majority of moderate-to-severe CAP patients showed similar or even better outcomes for oral treatment compared to intravenous treatment, but did not specify the disease severity for patients with treatment failure 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This was a population PK (PPK) substudy of the prospectively executed EXPO‐AB study. The EXPO‐AB study was a multicentre prospective intervention study, investigating the oral absorption of and systemic exposure to 2 single doses of amoxicillin or ciprofloxacin administered in addition to intravenous (IV) antibiotic treatment—during the febrile phase of infection and during convalescence, respectively—in noncritically ill hospitalized patients 14 . From the EXPO‐AB study population, we identified patients empirically treated with IV ceftriaxone.…”
Section: Methodsmentioning
confidence: 99%
“…At both study visits the subjects received a single oral dose of amoxicillin 750 mg or ciprofloxacin 500 mg for the purpose of the main study. At both visits, up to 4 blood samples were obtained according to the protocol of the EXPO‐AB study, 14 in which ceftriaxone could be measured besides amoxicillin and ciprofloxacin. This resulted in complete random sampling for the current ceftriaxone PPK substudy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fever and acute infection in non-critically ill patients do not seem to affect oral absorption of antibiotics when the infection is outside the gastrointestinal tract [10]. In addition, a retrospective study from two Brazilian intensive care units showed no difference in mortality when in-hospital step-down to oral antimicrobials was applied in initially septic patients (most often from pneumonia) that had reached clinical stability [11].…”
Section: Effect Of Acute Febrile Infection On Oral Antibiotic Absorptionmentioning
confidence: 99%